Mindfulness and Empathy: Mediating Factors and Gender Differences in a Spanish Sample - de la Fuente-Anuncibay, Raquel; González-Barbadillo, Ángela; Ortega-Sánchez, Delfín; Pizarro-Ruiz, Juan Pablo (Frontiers in Psychology, 2020)
Numerous research studies link mindfulness training to improved empathy. However, few studies focus on the mediating factors of empathy. This work has three objectives: (a) to analyze the possible mediation of mindfulness as a feature in this relation, (b) to analyze the mindfulness factors that mediate in the increase of empathy and (c) to analyze the moderating role of gender. The sample was composed of 246 Spanish-speaking university students (M = 24.08 years, SD = 8.43). The instruments used were the Five Facet Mindfulness Questionnaire (FFMQ) and the Toronto Empathy Questionnaire (TEQ). For data analysis, the indirect effect was calculated using 10000 bootstrap samples for the bias-corrected bootstrap confidence intervals (BCI). The improvement of empathy is mediated by the changes in mindfulness trait (B = 0.233, p < 0.001), disappearing in the presence of this mediator, the direct effect of mindfulness practice on empathy (B = 0.161, p = 0.394). We did not find a differential functioning of this mediation according to gender. Observing and describing are the FFMQ factors that mediate significantly between mindfulness practice and empathy.